Marketization in Space: Local and Regional Effects on Marketization in Denmark - Henrik Doensig Jørgensen; Torben Dall Schmidt (European Regional Science Association (ERSA), 2006)
New public economics has emphasized the importance of using market solutions in the public sector. Public-private partnerships and marketization through tender calls have been among the instruments of this policy trend. The regional and local effects of such policies are highly relevant for Denmark, as about 66 percent of the public budget in 2003 is delegated to municipalities and counties. The total public expenditures represent 55 percent of GDP in 2003 and are therefore a vital element in overall economic activity. These instruments from the new public economics thereby become active vehicles to local and regional development, which has to a high extent been delegated to local and regional authorities. They arguably constitute the most pronounced policy area within regional and local policies in Denmark. The hypothesis tested here is that marketization is a potent policy instrument for local and regional development in Denmark and that it is therefore important to plan for the operational areas to be subject to marketization. Using panel data on the use of tender calls by Danish municipalities for the period 1993-2004, the paper tests the extent to which the use of marketization influences the local and regional growth potentials, controlling for a number of local and regional characteristics. These growth potentials are measured through a number of indicators such as income growth, job growth and formation of new firms in different sectors. The findings indicate that marketization is most important policy tool in regional planning and development. Not only is it effective, but it is to a large extent also in the hands of local politicians. The slack in use of marketization among Danish municipalities and counties may therefore be a threat to overall growth at the local, regional and national level in Denmark.
Keywords: 330